Liberated art of living and surrealist subversion of proverbs according to Paul Éluard and Benjamin Péret - Bonhomme, Marc (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
Proverbs convey an idealized and conventional art of living that is generally referred to as popular wisdom. Made of stereotypes and pretending to shape our behaviour, this popular wisdom has been strongly contested by the surrealist poets Paul Éluard and Benjamin Péret in their 152 proverbes mis au goût du jour. On the one hand, this article analyzes the rhetorical modalities of this contest. These consist in a parody discourse that distorts traditional proverbs, while preserving their phraseology. On the other hand, this study examines how these parodic manipulations deconstruct the stereotypical art of living conveyed by the proverbial genre through different processes (trivialization, pejoration, contradiction, etc.). It also shows that the work of undermining carried out by Éluard and Péret on proverbs leads to the proclamation of a new art of living based on the poetic liberation of language, the refusal of authority and the reign of imagination.